벼 내냉성 증진 유전자의 염기서열 다형성 분석을 통한 통일형 품종의 하프로타입 분석 - 이영은; 이샛별; 강주원; 조준현; 박동수; 이종희; 신동진; 진병준 (Journal of plant biotechnology, 2024)
Rice is an important cereal crop worldwide. Domestic rice varieties in Korea are primarily of two types, namely Japonica varieties (table rice) and high-yield Tongil-type varieties. The domestically developed Tongil- type varieties have a 20-40% higher yield than the Japonica varieties. However, the Tongil-type varieties are more sensitive to cold temperatures than the Japonica varieties, which affects their cultivation adaptability. To improve the cold tolerance of Tongil-type varieties, genetic analysis was performed to identify 11 functionally validated cold tole- rance-enhancing genes, which were then subjected to haplotype analysis in both Japonica and Tongil-type rice varieties based on the data from the 3000 Rice Genome Project. An average of 10 haplotypes were identified for the 11 cold-tolerance genes in the Japonica and Tongil-type rice varieties. Notably, bZIP73 exhibited minimal polymorphism with only 4 haplotypes, while CTB2 showed the highest polymorphism with 31 identified haplotypes. To analyze the haplotypes of the cold tolerance-enhancing genes in the Tongil-type varieties, genomic information from 11 varieties, including Hanareum4 and Geumgang1, was extracted, and the single nucleotide polymorphisms (SNPs) at the same positions as the haplotypes were compared. All the Tongil- type varieties, except for Dasan1, contained haplotype 1 (Hap1) of the SAP16 gene, whose sequence was identical to that in the reference Japonica variety, Nipponbare, but distinct from that in the representative cold-tolerant variety, Jinbu. Additionally, the Miryang23, Geumgang, and Hanareum4 varieties possessed the same haplotypes of the HYPRP5 gene as the Nipponbare variety. Similarly, the Geumgang, Geumgang1, and Hanareum4 varieties possessed the same haplotypes as Nipponbare for the TCD5 gene. The results of this study can contribute to the development of SNP-specific molecular markers for improving the cold tolerance of Tongil-type varieties. KCI Citation Count: 0